Sexism - Perger, Nina (Teorija in praksa, 2016)
In this article, we analyse practices of naming sexism based on empirical data. The analysis is based on the concept of a "wilful subject" as discussed by Sara Ahmed. In the analysis, we are particularly interested in the contextual characteristics of naming sexism, that is, when and how does the naming occur, and when is the naming absent. We are also interested in the "backlashes" the one who is naming sexism is confronted with. Those backslashes function as attempts to legitimise already named and problematised sexism by addressing the subject doing the naming as a wilful one or a feminist killjoy. Thus, by naming a problem, the subject who is naming it may themselves become a problem.
Keywords: Higher education; Seksizem; Sexism; Subject; Subjekt; Visoko šolstvo